The meaning of prayer in Mary's messages of Medjugorje - Strehovec, Tadej (Edinost in dialog, 2025)
For decades, the apparitions of the Virgin Mary and pilgrimages to Medjugorje have aroused different opinions and positions in the Catholic Church and the public. After an introduction, the authors first outline the broader historical and socio-political context of the Marian apparitions in Medjugorje. Then they present the views of the Dicastery for the Doctrine of the Faith (DDF) on the apparitions in Medjugorje, with an in-depth analysis of the documents Norms for Proceeding in the Discernment of Alleged Supernatural Phenomena (2024) and The Queen of Peace: Note About the Spiritual Experience Connected with Medjugorje (2024), paying special attention to the understanding of prayer in the context of Medjugorje and its spiritual fruits in the context of the so-called Medjugorje phenomenon. In the fourth part, they analyse the content of the alleged messages of the Virgin Mary transmitted by the so-called seers, and in the last, fifth part, they focus on the meaning of prayer in Mary's messages of Medjugorje by analysing her calls to prayer through these messages. The article examines the role and importance of prayer as called for and encouraged by the Mother of God as the mediator between God and humanity, with special focus on her messages related to the events of the apparitions in Medjugorje. These invitations to prayer are in accordance with established Catholic doctrine, which considers prayer to be an essential means of communication with God and of receiving divine graces, thus promoting spiritual development. The originality of this scientific research lies in the evaluation of the meaning of prayer in Medjugorje in the context of Our Lady's messages and in the analysis of the position of the Dicastery for the Doctrine of the Faith, which in its evaluation of the apparitions of Mary officially emphasizes the spiritual (prayerful) fruits of the Medjugorje movement and relies on Our Lady's messages in its assessment. The authors use descriptive and analytical methods. They find it extremely interesting that the Holy See, in its official position, refers to the messages of Our Lady of Medjugorje in its assessment without yet confirming the apparitions of Mary. In a situation in which the Holy See has not (yet) officially confirmed the authenticity of the Marian apparitions, the authors do not deal with the authenticity of the messages and apparitions transmitted by the so-called seers, but underline the thesis that the spiritual fruits are most likely to determine the authenticity of the Medjugorje phenomenon, in which prayer on both personal and collective levels is of decisive importance.
Keywords: duhovnost; faith; Marian apparitions; Marija; Marijina prikazovanja; Marijina sporočila; Medjugorje; Medžugorje; messages of Virgin Mary; molitev; Naša Gospa; Our Lady; prayer; spirituality; vera